Prosedur Pengawasan oleh Majelis Pengawas Daerah terhadap Pelanggaran Administratif Berdasarkan Undang-Undang Jabatan Notaris di Kabupaten Serang - Nida Aulia; Nurikah Nurikah; Ahmad Rayhan Ahmad Rayhan (Journal of Legal, Political, and Humanistic Inquiry, 2026)
Supervision of notarial practices constitutes a crucial instrument in ensuring legal certainty and maintaining administrative order in the notarial office, as regulated under Law Number 2 of 2014 concerning Notary Position. However, notarial practices in Serang Regency still exhibit administrative violations, including breaches of territorial jurisdiction and non-compliance with administrative obligations, thereby creating a gap between normative provisions and practical implementation. This study aims to analyze the supervisory procedures carried out by the Regional Supervisory Council (Majelis Pengawas Daerah/MPD) of Serang Regency toward notaries committing administrative violations, as well as to identify the constraints encountered in its implementation. This research employs an empirical juridical approach with a descriptive qualitative method, utilizing primary data obtained through interviews and observations, and secondary data derived from statutory regulations and legal literature. The findings indicate that supervision is conducted through the examination of notarial protocols, summons and investigation processes, administrative guidance, and the provision of tiered administrative sanction recommendations. Nevertheless, its implementation has not been optimal due to various administrative, institutional, and resource-related constraints. Therefore, strengthening supervisory functions, enhancing institutional support, and improving notaries’ professionalism and legal awareness are essential.